2021
DOI: 10.1002/hbm.25755
|View full text |Cite
|
Sign up to set email alerts
|

Rapid processing and quantitative evaluation of structural brain scans for adaptive multimodal imaging

Abstract: Current neuroimaging acquisition and processing approaches tend to be optimised for quality rather than speed. However, rapid acquisition and processing of neuroimaging data can lead to novel neuroimaging paradigms, such as adaptive acquisition, where rapidly processed data is used to inform subsequent image acquisition steps. Here we first evaluate the impact of several processing steps on the processing time and quality of registration of manually labelled T1‐weighted MRI scans. Subsequently, we apply the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Both global and voxelwise analyses showed that grey matter, white matter and cerebrospinal fluid volumes are comparable between T 1 -w and EPImix T 1 -w scans. This extends our previous findings of correspondence between tissue intensities and Jacobian determinants (derived from registration of T 1 -w scans to MNI standard space), between EPImix and standard T 1 -w scans 7 . While Jacobian determinants can be derived relatively rapidly from T 1 -w scans, the primary constraint being the speed of non-linear registration, they are both less interpretable and less widely used than estimates of tissue volume.…”
Section: Tissue Volumesupporting
confidence: 88%
See 3 more Smart Citations
“…Both global and voxelwise analyses showed that grey matter, white matter and cerebrospinal fluid volumes are comparable between T 1 -w and EPImix T 1 -w scans. This extends our previous findings of correspondence between tissue intensities and Jacobian determinants (derived from registration of T 1 -w scans to MNI standard space), between EPImix and standard T 1 -w scans 7 . While Jacobian determinants can be derived relatively rapidly from T 1 -w scans, the primary constraint being the speed of non-linear registration, they are both less interpretable and less widely used than estimates of tissue volume.…”
Section: Tissue Volumesupporting
confidence: 88%
“…In this way, active acquisition holds the potential for reduced scan time and improved accuracy, reliability and individualisation of (neuro)imaging 16 . The main feasibility obstacles to active acquisition are the speed of image collection as well as data processing and analysis; to realise the benefits of this multimodal adaptive approach, analyses need to be carried out in near real-time 7,16 . Due to the relative speed of the new EPImix sequence, it could contribute considerably to this process.…”
Section: Active Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that many investigators have studied the proper ways to draw a null distribution. See, for example, Xia et al (2018) shuffled the networks in addition to permuting the labels to generate the null distribution; Zamani Esfahlani et al (2020) summarized different ways to create a null model that could preserve neuroanatomical realism; and more recently, Váša et al (2021) provided a comprehensive review on the logic, implementation and interpretation of null models for functional connectomes. Here, we have not shuffled the functional networks of the brain in order to preserve the underlying covariance structure of real biological data (Nichols & Hayasaka, 2016).…”
Section: Methodsmentioning
confidence: 99%